Human embryonic stem cells exert antitumor effects on prostate cancer cells in a co-culture microenvironment - Yang, Xinyue; Lu, Yang; Kuang, Qin; Wu, Yong; Tan, Xin; Lan, Jizhong; Qiang, Zhe; Feng, Tao (Frontiers in Oncology, 2023)
Prostate cancer is currently the most common malignancy among men. Given the limitations of current conventional anticancer therapies, new high-risk treatments are urgently needed. Previous studies have shown that embryonic stem cells (ESCs) can reverse the tumorigenic phenotype of tumor cells. However, there are still challenges in using human ESCs (hESCs) directly in cancer treatment. To facilitate the practical application of hESCs, we established a co-culture system consisting of prostate cancer cell lines and hESCs and investigated the antitumor activity of the supernatant of the co-culture system (Co-Sp) in vitro and in vivo, as well as the underlying mechanisms involved. The Co-Sp decreased the viability of prostate cancer cells in a concentration-dependent manner, significantly inhibited colony formation, and induced cell cycle arrest at the G0/G1 phase of the cell cycle. In addition, Co-Sp promoted apoptosis of prostate cancer cells and inhibited cell migration and invasion. In vivo studies also revealed that Co-Sp inhibited tumor growth in the xenograft model. Mechanistic studies showed that Co-Sp reduced the expression of cyclin D1, cyclin E, CDK4, CDK2, MMP-9, MMP-1, and Bcl-2, and increased the expression of p21, cleaved caspase-9, cleaved caspase-3, cleaved PARP, and Bax in prostate cancer cells. Furthermore, the Co-Sp decreased the phosphorylation of PI3K, AKT, and mTOR in cells and tumor tissues. Taken together, our results indicated that the Co-Sp has potent antitumor activity and could directly inhibit tumor growth. Our findings provide a new and effective way for the application of hESCs in cancer therapy and contribute to a new strategy for clinical stem cell therapy.